Hypermongone C Accelerates Wound Healing through the Modulation of Inflammatory Factors and Promotion of Fibroblast Migration - Moghadam, Sara E. (Molecules, 2019)
The physiology of wound healing is dependent on the crosstalk between inflammatory mediators and cellular components of skin regeneration including fibroblasts and endothelial cells. Therefore, strategies to promote healing must regulate this crosstalk to achieve maximum efficacy. In light of the remarkable potential of natural compounds to target multiple signaling mechanisms, this study aims to demonstrate the potential of hypermongone C, a polycyclic polyprenylated acylphloroglucinol (PPAP), to accelerate wound closure by concurrently enhancing fibroblast proliferation and migration, promoting angiogenesis, and suppressing pro-inflammatory cytokines. This compound belongs to a family of plants (Hypericum) that traditionally have been used to treat injuries. Nevertheless, the exact biological evidence to support the claims is still missing. The results were obtained using a traditional model of cell scratch assay and endothelial cell tube formation, combined with the analysis of protein and gene expression by macrophages. In summary, the data suggest that hypermongone C is a multi-targeting therapeutic natural compound for the promotion of tissue repair and the regulation of inflammation.